Strategies for crisis and risk management in sustainable construction: communication and green culture in Pakistan - Sheikh Kamran Abid; Ahmed M Al-Wathinani; Krzysztof Goniewicz (Environmental Research Communications)
The Pakistani construction industry faces significant challenges that hinder project success, including poor risk management, communication gaps, a lack of organizational cohesion, and inadequate green human resource management practices. This study investigates the impact of these critical factors on project outcomes within Pakistan’s unique economic and regulatory landscape. Using semi-structured interviews with project managers across various construction firms, we conducted a thematic analysis to explore how proactive risk management, effective communication strategies, a supportive green organizational culture, and green strategic human resource management practices contribute to project durability of the building and timely completion. The durability of a building entails the utilization of long-lasting resources, environmentally friendly building processes, and ideas that maintain the structure so that it stays operational and practical for its planned duration. Findings reveal that comprehensive crisis and risk management minimizes disruptions and budget overruns, while robust communication management reduces misunderstandings, fostering collaboration and efficiency. Furthermore, a positive green organizational culture enhances teamwork and motivation and targeted green human resource strategies support skill alignment and improve workforce performance. This study provides actionable insights for construction firms in Pakistan aiming to optimize green management strategies to enhance project success rates, suggesting that an integrated approach to risk, communication, green culture, and green human resource practices is essential to meet the demands of this growing sector.